The Effect of Tax-Exempt Investors and Risk on Stock Ownership and Expected Returns - Guenther, David A.; Sansing, Richard (The Accounting Review, 2010)
ABSTRACT: We investigate how shareholder taxes and risk preferences affect both a stock’s expected return, which reflects the capitalization of the dividend tax penalty into stock price, and the fraction of a firm’s stock held by tax-exempt investors. Our model demonstrates that the dividend tax capitalization effect reflects the weighted average tax rate of all investors, where the weighting depends on investors’ risk tolerances. This weighted average tax rate is not affected by the fraction of stock held by tax-exempt investors; however, tax-exempt investor ownership can be correlated with the weighted average tax rate if differences in tax-exempt investor ownership for different stocks reflect differences in investor risk tolerances for those stocks. Our empirical tests are consistent with the model’s predictions, and provide an equilibrium framework for interpreting prior empirical studies in accounting.